2020
DOI: 10.1097/mjt.0000000000001295
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Hospitalized COVID-19 Patients

Abstract: Background: Venous thromboembolism (VTE) is increasingly reported in seriously ill patients with COVID-19 infection. Incidence of VTE has been reported before and results varied widely in study cohorts. Area of uncertainty: Incidence of major VTE (segmental pulmonary embolism and above and proximal deep vein thrombosis) which is a contributor to mortality and morbidity is not known. Also, data is unclear on the optimal anticoagulation regimen to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
19
0
3
Order By: Relevance
“…Patients who need to be admitted to hospital should have a prescription for thromboprophylaxis unless contraindicated, but the best effective dosage remains uncertain [ 29 ]. A recent meta-analysis suggested better primary prevention of VTE by using curative versus prophylactic anticoagulation [ 30 ]. However, the expected benefit on survival following curative versus prophylactic dosing regimen (standard vs. high) still remains controversial [ 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who need to be admitted to hospital should have a prescription for thromboprophylaxis unless contraindicated, but the best effective dosage remains uncertain [ 29 ]. A recent meta-analysis suggested better primary prevention of VTE by using curative versus prophylactic anticoagulation [ 30 ]. However, the expected benefit on survival following curative versus prophylactic dosing regimen (standard vs. high) still remains controversial [ 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While every effort is being made by the medical experts to treat patients by taking suitable preventive measures employing anticoagulation therapeutics to deal with the coagulation issues. Despite superb benefits with the use of systemic anticoagulation therapies, the data seem to be retrospective in nature thus raising some questions on the possible interplay of other confounders, as well as, long-term benefits and safety of the systemic anticoagulation approach [26][27][28][29][30][31][32][33][34].…”
Section: Proteinase and Covid-19mentioning
confidence: 99%
“…However, only few of the included studies were of good quality and no information was provided regarding various age groups. A meta-analysis of hospitalised COVID-19 patients showed that anticoagulation in therapeutic dose was beneficial [ 80 ]. An analysis of 4389 hospitalised COVID-19 adults found that anticoagulation was associated with lower mortality and intubation, with a trend towards a higher benefit with therapeutic doses [ 81 ].…”
Section: Anticoagulantsmentioning
confidence: 99%